Evaluation of the use of sunflower (Helianthus annuus) in phytoremediation of PB, CU and ZN in soil - Oliveira, Luísa Helena dos Santos; Luiz, Evandro Pereira (Revista Hipótese, 2018)
The present work evaluated the phytoremediation in the removal of Pb, Cu and Zn present in the soil, with samples prepared in laboratory at known concentrations of each heavy metal using sunflower. The removed metal contents were analyzed by atomic emission spectrometry. The sunflower removed the three metals, with rates higher than 40% in all samples, proving to be efficient and a solution of low financial cost and environmental impact for contaminated sites.